An examination of the role of oxygen in the wear of ferrous alloys - Srivastava, Vinod Kumar. (1974)
Thesis (Ph.D.) -- Memorial University of Newfoundland. 1975. Engineering and Applied Science Bibliography : leaves 217-221.